Overview of infectious salmon anaemia virus (ISAV) in Atlantic Canada and first report of an ISAV North American‐HPR0 subtype. Issue 3 (7th August 2017) - Gagné, N; LeBlanc, F
Abstract: The infectious salmon anaemia virus (ISAV) is an important viral disease of farmed Atlantic salmon that has caused considerable financial losses for salmon farmers around the world, including Atlantic Canada. It is listed as a notifiable disease by the World Organization for Animal Health, and to this day, culling of infected cages or farms remains the current practice in many countries to mitigate the spread of the virus. In Atlantic Canada, ISAV was first detected in 1996 and continues to be detected. While some outbreaks seemed to have arisen from isolated infections of unknown source, others were local clusters resulting from horizontal spread of infection. This study provides a description of the detected ISAV isolates in Atlantic Canada between 2012 and 2016, and explores the phylogenetic relatedness between these ISAV isolates. A key finding is the detection for the first time of a North American‐HPR0 ISAV subtype, which was predicted to exist for many years. Through phylogenetic analysis, a scenario emerges with at least three separate incursions of ISAV in Atlantic Canada. An initial ISAV introduction follows a genotypic separation between North America and Europe which resulted in the NA and EU genotypes known today; this separation predates the salmon aquaculture industry. The second incursion of ISAV from Europe to North America led to a sublineage in Atlantic Canada consisting of EU‐HPR∆ isolates detected in Nova Scotia and New Brunswick, and the predominant form of ISAV‐HPR0 (EU). Finally, we observed what could be the third and most recent incursion of ISAV in Newfoundland, in the form of an isolate highly similar to ISAV EU‐HPR0 isolates found in the Faroe Islands and the one isolate from Norway.